DYNAMICS OF CONSUMER PAYMENT PREFERENCES: AN EXPLORATION OF THE ROLE OF MENTAL ACCOUNTING IN PER-USE SERVICE RATES - Aripin, Zaenal; Ermeila, Sri; Alfian, Achmad (KRIEZ ACADEMY : Journal of development and community service, 2024)
Dynamics of Consumer Payment Preferences: Exploring the Role of Mental Accounting in Per-Use Service Fees is an interesting topic in the study of consumer behavior. This research aims to understand how mental accounting influences consumer payment preferences in the context of per-use service fees. The concept of mental accounting encompasses the way individuals process financial information and make purchasing decisions based on their mental representation of financial circumstances. Per-use service fees offer a payment model that allows consumers to pay based on their actual usage, which is considered more fair and efficient. However, consumer payment preferences are also influenced by psychological factors such as perceived value, control, and fairness. Qualitative research and content analysis are used to explore the dynamics of consumer payment preferences in this context. The results show that mental accounting plays an important role in how consumers evaluate and choose per-use service rates. Psychological factors such as perceived value, control, and fairness also influence consumer payment preferences. The implication of these findings is the importance of paying attention to psychological factors in designing effective tariff strategies and understanding complex consumer behavior. By understanding how mental accounting and other psychological factors influence consumer payment preferences, business practitioners can develop more effective marketing strategies and increase consumer satisfaction in an increasingly dynamic and competitive marketplace.